Old and cosmopolite: molecular phylogeny of tropical-subtropical kites (Aves: Elaninae) with taxonomic implications - Starikov, Ivan J.; Wink, Michael (Diversity, 2020)
Kites of the Elaninae group are small and medium-sized, mostly tropical raptors traditionally considered as an early diverged subfamily of the Accipitridae. We used nucleotide sequences of three genetic markers (mitochondrial Cyt b and COI, nuclear RAG-1) to reconstruct the phylogenetic relationships of the Elaninae, other kites, and representatives of different families of diurnal raptors. Our results confirm the basal position of Elaninae, separated the latest in Early Miocene, including Chelictinia riocourii, which was not sequenced before and belongs to this group. Not only DNA data but also cytological, morphological, and ecological data show the singularity of Elaninae. We suggest elevating this group to family level as Elanidae within the order Accipitriformes. It includes Gampsonyx swainsonii as a monotypic subfamily because of distinctive traits and DNA sequence data. Taxonomic implications for other macrogroups of Accipitriformes are discussed.